2004
DOI: 10.1590/s0034-72992004000400014
|View full text |Cite
|
Sign up to set email alerts
|

Reconhecimento de fala no ruído em jovens e idosos com perda auditiva

Abstract: Palavras-chave: percepção da fala, teste de fala em ruído, audição.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
25

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 12 publications
5
42
0
25
Order By: Relevance
“…These findings are similar to other studies [29][30][31][32][33][34][35][36] , contributing to the understanding of presbycusis, generally speaking, and how it affects this population.…”
Section: Figure 2 -Comparison Between Er-3a and Tdh-39 Earphones In Wrssupporting
confidence: 91%
“…These findings are similar to other studies [29][30][31][32][33][34][35][36] , contributing to the understanding of presbycusis, generally speaking, and how it affects this population.…”
Section: Figure 2 -Comparison Between Er-3a and Tdh-39 Earphones In Wrssupporting
confidence: 91%
“…In the case of closing and figure-background for verbal sounds skills, one study 17 that evaluated speech recognition in noise in the elderly revealed that these, especially with hearing loss, as EV and IC, presented worse performance with relation to speech perception in noise. Another study 9 conducted with elderly 60-84 years old revealed that the age and degree of hearing loss were significant (especially in the elderly over 80 years old) in the results obtained in the assessment of auditory processing, especially in closing and figure background for verbal sounds skills, which can be to talk, asking how long it would take, demonstrating a certain inattention during the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is believed that there are a number of individual factors to be considered in quiet situations, including memory, intelligence, interest and level of stress of the subject 16,17 . Furthermore, it is also noted that when the seniors listen to the radio or watch television in quiet environments, other factors may be involved beyond the hearing threshold, such as the reduction of visual cues, speech rate increased and lack of contextualization of what is said…”
Section: Discussionmentioning
confidence: 99%